A bibliometric review of energy justice literature - Ferrall-Wolf, Isa; Gill-Wiehl, Annelise; Kammen, Daniel M. (Frontiers in Sustainable Energy Policy, 2023)
Academic literature on energy justice sits at the intersection of a complex ecosystem of technologies, geographies, disciplinary traditions, terminologies, frameworks, theories, and methods. Its recent and rapid growth suggests its interest to a large number of stakeholders. However, these same features make aggregation and summarization a considerable undertaking. This paper uses advanced bibliometric analytics to synthesize this disparate and varied metadata to characterize trends in the academic literature's treatment of energy justice. This review covers 4,196 papers published between 1983 and 2023 with methods appropriate to the number and diversity of publications and associated sub-fields. We document distinct usages of similar terminologies across subfields in the literature, inequitable ratios of global research compared to absolute levels of energy poverty, and the large but under-recognized contribution of cooking to the energy justice literature. In summarizing this voluminous literature and analyzing thematic changes over time we provide a scaffolding for more detailed reviews to place themselves within the larger interconnected literature network.